Implementasi Undang-Undang Nomor 41 Tahun 2009 Tentang Perlindungan Lahan Pertanian Pangan Berkelanjutan Terkait Konservasi Lahan Pertanian Di Kabupaten Bolaang Mongondow - Moh Vazri Damopolii; Fenty U.Puluhulawa; Zamroni Abdussamad (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study aims to determine the implementation of Law No. 41 of 2009 concerning Protection of Sustainable Food Agriculture Land in Surakarta City and its obstacles. Research background, that the development of food security and sovereignty needs to be carried out through the provision and establishment of sustainable food agricultural land. But in urban areas, efforts to maintain the existence of agricultural land are quite complicated problems. The high demand for land due to the development of housing, trade, services, industry and others causes a large proportion of the agricultural area to continue to decline every year. The promulgation of Law No. 41 of 2009 concerning Protection of Sustainable Food Agriculture Land is expected to reduce the high rate of conversion of rice fields and maintain their ecological functions. This type of research is an empirical legal research. The nature of the research is descriptive because it wants to describe the implementation of Law Number 41 of 2009 concerning Protection of Sustainable Food Agriculture Land in Surakarta City. The results of the study, that the implementation of Law Number 41 of 2009 concerning Land Sustainable food agriculture in the City of Surakarta was only at the stage of inventorying paddy fields and had not yet arrived at the formation of a Regional Regulation. The reason is that paddy fields in the city of Surakarta are not productive because there is no technical irrigation network available, the majority of the livelihoods of the people of Surakarta are not as farmers, and the high demands of settlement needs as a consequence of the development of urban areas. This is in accordance with the results of identification by the Department of Agriculture, BPN and BAPPEDA that out of 111 hectares of agricultural land listed in the Regional Spatial Planning of Surakarta City No. 1 of 2012, the total area of agricultural land is less than 111 hectares and only 80-90 hectares of land. agriculture that is not cultivated and partly in the form of paddy fields surrounded by housing. The absence of a regional regulation that stipulates the protection of sustainable agricultural land causes in practice there is no clarity regarding protected land, sanctions for violations or incentives that will be accepted by the community if they do not carry out or protect the agricultural land they own.